Educação e tecnologia: o telefone celular como recurso de aprendizagem - Márcia Gorett Ribeiro Grossi; Letícia Carvalho Belchior Emerick Fernandes (EccoS – Revista Científica)
Among digital technologies of information and communication (TDICs) currently available in the educational process, the mobile phone stands out with its various functions such as photographic and video cameras, message service, bluetooth, notepad and internet access. In this perspective, the aim of this paper was to determine how this technology is being used as a learning resource. The method used was a cases study conducted in two high schools in the city of Belo Horizonte/ Brazil, one public and the other private, focusing on a qualitative approach. The research instrument was a questionnaire. The results reveal that the portable media are a reality in everyday life of these two institutions, and the resources available on the mobile phone allow several didactic applications. The challenge for the teacher is to reflect on the integration of these technologies in the learning process, preparing interactive and dynamic lessons for the new requirements imposed by Internet Generation.